Appropriateness of admission and stay in obstetrics wards: a new tool assessing unnecessary days of hospital care (Italian Journal of Public Health, 2009)
Introduction: The Appropriateness Evaluation Protocol (AEP) is a widely used assessment tool that identifies and measures the inappropriateness variables of hospital healthcare related to unjustified admission and/or length of stay, however it does not apply specifically to gynaecology or obstetrics wards. Objectives of the study: The main objectives of the present study were to develop a new tool for the evaluation of the appropriateness of admission and hospital stay in obstetric settings; as well as to analyze the main determinants of inappropriate admission and days of hospital stay within all the units of the Pediatric Hospital “Regina Margherita” and the Obstetrics and Gynaecology Teaching Hospital “S.Anna” in Turin.Methods: A multidisciplinary team of reviewers, composed of gynaecologists, paediatricians and obstetricians, was established and the appropriateness evaluation criteria, the operational handbook and the plan were all defined. Data were collected during the period between September and December 2005 and then put in an ad hoc database. Data analysis and evaluation were performed by univariate analysis (chisquare test) and multivariate analysis using a multiple logistic regression model. The level of significance was set at p
Keywords: appropriateness evaluation protocol; appropriateness of admission; appropriateness of stay; obstetric unit